THE IMPORTANCE OF LEARNING THE GERMAN LANGUAGE IN THE MODERN WORLD - Sharofat Nematullayevna Begasheva (International Journal of Literature and Language Studies, 2026)
This article examines the role of role-playing games in teaching German as a foreign language. Role-playing activities are considered an effective pedagogical tool that promotes the development of students’ communicative competence, speaking skills, and intercultural awareness. The study discusses the main types of role-playing games used in German language lessons, including situational, professional, and discussion-based activities. Special attention is paid to the stages of organizing role-playing tasks and their impact on learners’ motivation and active participation in the educational process. The article concludes that the systematic use of role-playing games creates a communicative learning environment, enhances language acquisition, and prepares students for real-life interactions in German-speaking contexts.